2021
DOI: 10.1080/15472450.2021.1901225
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a vehicle’s route in an on-demand ridesharing system in which users might walk

Abstract: Within the context of a shared on-demand transport system, we study the problem of selecting the stopping points from which passengers should walk to their exact destinations (or from their exact origins). We focus on the single-vehicle case that must follow a predefined order of requests, posing the mathematical program, showing that it can be solved in polynomial time and proposing a heuristic that runs faster. We compare the optimal algorithm, the heuristic, and the routes that visit the exact request point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…To analyze the qualitative effects of stop pooling on the collective dynamics of ride sharing and in particular how stop pooling changes fluctuations in the travel time, we introduce an event-based model (details in supplementary note 1 and 2 citing [16][17][18][19][20][21][22][23][24] and in [15]) with three different events: (i) users request trips from an origin to a destination, (ii) ride sharing buses pickup users and (iii) deliver them. New users request trips while buses serve other users.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the qualitative effects of stop pooling on the collective dynamics of ride sharing and in particular how stop pooling changes fluctuations in the travel time, we introduce an event-based model (details in supplementary note 1 and 2 citing [16][17][18][19][20][21][22][23][24] and in [15]) with three different events: (i) users request trips from an origin to a destination, (ii) ride sharing buses pickup users and (iii) deliver them. New users request trips while buses serve other users.…”
Section: Methodsmentioning
confidence: 99%
“…When taking a shared trip with multiple riders, the PUDO optimization is vital to prevent pointless detours. Whereas in the conventional system, the vehicle is frequently obliged to pick up passengers at certain locations [15]. Detours are made in order to pick up additional riders frequently result in longer travel times and higher costs.…”
Section: B Motivationmentioning
confidence: 99%
“…Such an approach was tested by Fielbaum et al (2021), showing that it can improve the level of service and decrease the total travel time. Later, Fielbaum (2021) tried optimizing pickup and drop-off positions of precomputed vehicle plans to measure the benefits exactly. He demonstrated that we could decrease the travel cost by almost 19% when optimizing the locations with a heuristic method and 24% with a slower optimal solution method.…”
Section: Related Workmentioning
confidence: 99%